Broken promises: an unconventional view of what went wrong at IBM / by D. Quinn Mills and Bruce Friesen - "Mills, D. Quinn" (Boston, 1996)
Mills and Friesen examine what caused IBM to experience major financial losses and the need to reduce its staff by half. Virtually overnight, IBM went from being one of the most respected firms in the world to one widely condemned. This book describes how the company's violation of two well-established contracts led to its most serious problems. The first was its long-standing relationship with customers, where the implicit agreement was IBM's guarantee of high-quality technology and close service support. The second was between IBM and its employees, with the implicit commitment to employee security. When IBM abrogated both contracts in the 1980s, its business began to fall apart. Quinn and Friesen describe IBM's experience in terms of broader historical and contextual patterns, and they look at the strategic tasks that IBM now confronts during its comeback. "Mills and Friesen" argue their case cogently and clearly.
Keywords: International Business Machines Corporation